THE ROLE OF MODAL VERBS IN ENGLISH GRAMMAR (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the role of modal verbs in English grammar. Modal verbs are essential in expressing probability, permission, obligation, and other nuances of action. The article explains their functions, usage, types, and differences from other verbs with relevant examples. Understanding and properly using modal verbs significantly contributes to improving language competence in English learners.